2020
DOI: 10.1044/2020_jslhr-19-00167
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Effects on Language in Children With Autism: A Project AIM Meta-Analysis

Abstract: Purpose This study synthesized effects of interventions on language outcomes of young children (ages 0–8 years) with autism and evaluated the extent to which summary effects varied by intervention, participant, and outcome characteristics. Method A subset of effect sizes gathered for a larger meta-analysis (the Autism Intervention Meta-analysis or Project AIM) examining the effects of interventions for young children with autism, which were specific to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 127 publications
1
67
1
2
Order By: Relevance
“…Though the logical framework of these theories suggests that children with autism should receive intervention as early as possible to capitalize on periods during which we should expect optimal plasticity, intervention research has not definitively shown that children who receive intervention at younger ages benefit more than those who begin intervention later in life. In fact, several previous meta‐analyses of early interventions for children with autism have found that chronological age at intervention was not a significant moderator of intervention effects on outcomes of interest [Makrygianni & Reed, 2010; Reichow & Wolery, 2009; Sandbank et al, 2020b; Virués‐Ortega, 2010].…”
Section: Factors That May Influence Intervention Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the logical framework of these theories suggests that children with autism should receive intervention as early as possible to capitalize on periods during which we should expect optimal plasticity, intervention research has not definitively shown that children who receive intervention at younger ages benefit more than those who begin intervention later in life. In fact, several previous meta‐analyses of early interventions for children with autism have found that chronological age at intervention was not a significant moderator of intervention effects on outcomes of interest [Makrygianni & Reed, 2010; Reichow & Wolery, 2009; Sandbank et al, 2020b; Virués‐Ortega, 2010].…”
Section: Factors That May Influence Intervention Effectsmentioning
confidence: 99%
“…Intervention effects may vary as a function of child language level at the start of intervention. Previous investigations have found that children with higher language level at intervention onset tend to demonstrate larger gains than their counterparts with lower language level [Bono, Daley, & Sigman, 2004; Itzchak & Zachor, 2011; Sandbank, Bottema‐Beutel, Crowley, et al, 2020b]. This may be because children with more advanced language levels have more tools to help them engage in a social dyad with the interventionist administering an NDBI, which is where much (or all) learning is expected to take place.…”
Section: Factors That May Influence Intervention Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers could refer to existing metaanalyses on early intervention for some insight into evidence of e cacy (e.g. (Sandbank et al, 2020)). Finally, due to the extent and variation of speci c outcome measures used in autism research and clinical practice, we have not reported the exact measurement tools that studies used within these domains.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As early as the 1980s, intervention researchers have sought to modify how caregivers speak to their autistic children in an effort to positively influence autistic children's development [e.g., Harris, Wolchik, & Milch, 1982]. Because caregivers spend more time with their children than clinicians, coaching caregivers to talk to their children in particular ways is a promising intervention strategy [Sandbank et al, 2020b]. Recently, these interventions have focused on increasing caregiver talk that is responsive to children's behavior, and elicits their participation in interactions of increasing duration and complexity.…”
Section: Introductionmentioning
confidence: 99%